The gap between teachers’ English proficiency, necessity and online learning skills in the COVID-19 pandemic - Hadiyanto; Mukminin, Amirul; Ali, Raden Muhammad; Fauzan, Muhammad; Wulandari, Sovia (Nurture, 2023)
Purpose: This study aims to investigate the relationship between teachers’ perceived necessity and their online learning skills during the COVID-19 pandemic in Indonesia. It focuses on four key elements of online course design: course communication, resource authenticity, time management and technical skills. Design/Methodology/Approach: A quantitative survey was used to collect data from 39 teachers using the Survey Monkey application and manual returns. The data was collected through five Likert- scale questionnaires. Finding: The findings showed a significant discrepancy between teachers’ perceived necessity and their actual online learning skills. The mean score for teachers’ perceived necessity for online learning was at the highest level while their actual skills were at the lowest. A positive correlation between English proficiency and teachers’ online learning skills was found. Further analysis demonstrated a significant relationship between English proficiency and teachers’ online learning skills. Conclusion: Teachers perceived the necessity for online learning skills as crucial as their actual skills were found to be limited or low during the pandemic. Furthermore, the study demonstrated that English proficiency skills positively impact teachers’ online learning skills. Research Limitations: It is recommended to carry out a more extensive investigation involving a larger population to obtain generalizable results. Practical Implication: The result indicates that teacher training in online learning skills is crucial in preparation for the future. The study informs the policymaker to consider further emergency situations related to the full online learning policy. Contribution to Literature: This study highlights the importance of English proficiency in the development of online teaching skills.